Statistical Modeling of Tear Strength for One Step Fixation Process of Reactive Printing and Easy Care Finishing - Asim, Fareha; Mahmood, Muzzaffar (Mehran University Research Journal of Engineering and Technology, 2017)
Statistical modeling imparts significant role in predicting the impact of potential factors affecting the one step fixation process of reactive printing and easy care finishing. Investigation of significant factors on tear strength of cotton fabric for single step fixation of reactive printing and easy care finishing has been carried out in this research work using experimental design technique. The potential design factors were; concentration of reactive dye, concentration of crease resistant, fixation method and fixation temperature. The experiments were designed using DoE (Design of Experiment) and analyzed through software Design Expert. The detailed analysis of significant factors and interactions including ANOVA (Analysis of Variance), residuals, model accuracy and statistical model for tear strength has been presented. The interaction and contour plots of vital factors has been examined. It has been found from the statistical analysis that each factor has an interaction with other factor. Most of the investigated factors showed curvature effect on other factor. After critical examination of significant plots, quadratic model of tear strength with significant terms and their interaction at Î± = 0.05 has been developed. The calculated correlation coefficient, R2 of the developed model is 0.9056. The high values of correlation coefficient inferred that developed equation of tear strength will precisely predict the tear strength over the range of values